Pendampingan Siswa dalam Festival Edukasi Lingkungan (FEELING) Menuju Trenggalekzero Net Carbon 2025 - Fahrudin Fahrudin; Ayu Agustin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
In an effort to achieve a Zero Net Carbon target in Trenggalek, the Trenggalek Regency Government, initiated by the Indonesian Adiwiyata Activists Association (HPAI), held an Environmental Education Festival (FEELING). Various competitions were held during the festival. One of the competitions was an environmental poster-making competition. Posters are visual publications that use images, text, or a combination of both to convey messages or information to the general public. The competition was carefully structured so that activities were tailored to different educational levels. The competition was open to elementary, middle, and high school/vocational school students